3D printing biocompatible materials with multi jet fusion for bioreactor applications - Priyadarshini, Balasankar Meera (2023)
In the evolving three-dimensional (3D) printing technology, the involvement of different materials in any new 3D printing process necessitates a thorough evaluation of the product's biocompatibility for biomedical application. Here, we examined the ability of Multi Jet Fusion (MJF)-printed PA-12 to support cell proliferation and osteogenesis. Our results show that leachate from MJF-printed PA-12 does not inhibit the growth of L929 fibroblast and MC3T3e1 osteoblast. The substrate supports the attachment and proliferation of both cell types, though not at a level comparable to conventional polystyrene culture plate. Neither plasma treatment, poly-D-lysine, nor collagen coatings narrowed the gap substantially, suggesting the possible influence of other limiting factors. The substrate can also support MC3T3e1 osteogenesis. However, MJF-printed PA-12 exhibits varying ability in supporting the proliferation of different cell types, especially in subsequent passages. While L929's proliferation is comparable from passage-to-passage, MC3T3e1's growth ability is noticeably compromised. Interestingly, our results show that L929 subcultured back to polystyrene plate retains the ability to grow as robustly as those on the conventional plate, suggesting that MJF-printed PA-12 does not permanently impair cell proliferation. In addition, we have shown the successful culture of bacterial Escherichia coli on MJF-printed PA-12. Together, our study demonstrated the potential of MJF-printed PA-12 for biological applications.